2022
DOI: 10.3389/fpsyg.2022.970466
|View full text |Cite
|
Sign up to set email alerts
|

Are depression and suffering distinct? An empirical analysis

Abstract: Depression and the subjective experience of suffering are distinct forms of distress, but they are sometimes commingled with one another. Using a cross-sectional sample of flight attendants (n = 4,652), we tested for further empirical evidence distinguishing depression and suffering. Correlations with 15 indices covering several dimensions of well-being (i.e., physical health, emotional well-being, psychological well-being, character strengths, social well-being, financial/material well-being) indicated that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In summary, the influence of cultural perceptions needs to exist and be maintained in behavioral interactions. The synthesis of the three theoretical perspective variables described above goes beyond Xiang's perspective (2021) of explaining the tendency to break off relatives and weakening the impact of this phenomenon purely in terms of modern social transformation, while also integrating Hu's meso-interpretation (2022) of the phenomenon of breaking off relatives as viewed from the perspective of intra-familial social comparisons and pressures, and at the same time Sun's proposal (2023) advocating an explanation of this phenomenon in terms of moral culture, class mobility, and social relations. It is a continuation and synthesis of existing Chinese intellectual discussions on this issue, and it also hopes to provide a comparative case for the explanation of such phenomena in different socio-cultural contexts around the world.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the influence of cultural perceptions needs to exist and be maintained in behavioral interactions. The synthesis of the three theoretical perspective variables described above goes beyond Xiang's perspective (2021) of explaining the tendency to break off relatives and weakening the impact of this phenomenon purely in terms of modern social transformation, while also integrating Hu's meso-interpretation (2022) of the phenomenon of breaking off relatives as viewed from the perspective of intra-familial social comparisons and pressures, and at the same time Sun's proposal (2023) advocating an explanation of this phenomenon in terms of moral culture, class mobility, and social relations. It is a continuation and synthesis of existing Chinese intellectual discussions on this issue, and it also hopes to provide a comparative case for the explanation of such phenomena in different socio-cultural contexts around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cowden et al 2 showed that suffering is associated with lower subsequent psychological flourishing even after adjusting for (amongst other factors) symptoms of anxiety and depression. These findings indicate that suffering is a distinct negative affective experience, and that its presence could have clinically significant implications for individual well-being 12,21 .…”
mentioning
confidence: 82%
“…Refs. 61 63 . Respondents respond to two questions: In general, how would you rate your physical health?…”
Section: Methodsmentioning
confidence: 99%